Processing dewatered sewage sludge using electro-kinetic (EK) technology - Tan, Jeremy Wee Chuang. (2013)
Sludge dewatering applications have gained prominence in the wastewater treatment industry in recent years. Currently, the dewatered sludge from sewage treatment plants contains high water content (around 80%), which is not suitable for its immediate use or disposal. This has led to significant advances in sludge dewatering processes that have evolved over the last decades. Presently, electro-kinetics (EK) is seen as a promising and efficient technology which is capable of removing substantial amount of water from municipal or industrial sludge. Large quantities of liquid can be extracted from sludge and this typically translates into a volume reduction of 50-70%. Furthermore, various R&D studies have been carried out to improve on the existing systems or to explore more effective dewatering techniques. In this research project, various pretreatment techniques such as ultrasound, heating and nanoparticles were carried out on raw sludge to improve its dewatering ability and further optimize the EK system. The goal is to enhance the electro-dewatering efficiency and increase the moisture removal, as well as to obtain higher final solids content of the sludge cake. Excess moisture removal leads to further reduction in transportation and disposal costs due to smaller volumes while maintaining an economical balance for sustainable sludge management.